2019
DOI: 10.1016/j.heliyon.2019.e02127
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of frog skin to chemicals: effect of penetration enhancers

Abstract: Rarely do commercial chemical products contain solely the active chemical/ingredient. It is therefore important to consider whether ingredients other than the active may: 1) alter absorption of the active chemical, or 2) be absorbed themselves, resulting in systemic effects. Frogs have highly permeable skin and are routinely exposed to commercial chemical products in the environment or therapeutically. Ethanol and propylene glycol (PG), which have known penetration-enhancing effects, are commonly included in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…This results in loosening the lipid layer and increasing its uidity and consequently increases the degree of diffusion of active compounds. 59,63 Almost for each compound, there is the same tendency of an increase in the cumulative mass of ibuprofen that permeated through the skin, expressed as mg IBU cm À2 , with the change of the alcohol as a vehicle, in the sequence from methanol through ethanol to i-propanol, for both acceptors phases pH 5.4 and 7.4 (Table 4). It means, that i-propanol is the best enhancer of skin permeation of both unmodied ibuprofen and its salts with L- ).…”
Section: Skin Permeation and Accumulationmentioning
confidence: 92%
“…This results in loosening the lipid layer and increasing its uidity and consequently increases the degree of diffusion of active compounds. 59,63 Almost for each compound, there is the same tendency of an increase in the cumulative mass of ibuprofen that permeated through the skin, expressed as mg IBU cm À2 , with the change of the alcohol as a vehicle, in the sequence from methanol through ethanol to i-propanol, for both acceptors phases pH 5.4 and 7.4 (Table 4). It means, that i-propanol is the best enhancer of skin permeation of both unmodied ibuprofen and its salts with L- ).…”
Section: Skin Permeation and Accumulationmentioning
confidence: 92%
“…As reduced exposure time would be of benefit in a clinical situation, the addition of 20%v/v PG as a penetration enhancer was considered to increase absorption rate. Our previous study reported a relationship between logP and the enhancement ratio (ER) for model chemicals when applied to the ventral pelvis in cane toads [ 36 ]. Thus, it is expected that the absorption rate from this formulation will increase according to this relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we developed in vitro models of absorption in the cane toad ( Rhinella marina ) based on three model chemicals, and determined how well the models’ predictions of absorption matched the in vivo absorption of the same chemicals [ 35 ]. We have also reported the impact of penetration enhancers on absorption through frog skin [ 36 ]. The broad aim of this study is to determine the utility of these previous results in predicting the in vivo percutaneous absorption of a drug for treatment of infectious disease in frogs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the masking effects of concurrent elimination processes occurring in vivo, the assumption that flux is constant from the start of dosing when predicting serum concentrations is another potential source of error. A lag-phase has only been reported in frog skin in vitro when the donor solution contains penetration enhancers [ 33 ]; as the first sample in the current study was taken at 30 minutes, it is possible that the lag phase occurred prior to this sample being taken. Disregarding even a short lag-time when predicting serum concentration would contribute to the disparity between in vitro predictions and in vivo concentrations.…”
Section: Discussionmentioning
confidence: 99%